Pelaksanaan Sistem Pembelajaran Tuntas di Madrasah Aliyah Negeri 3 Jember: Implementation of Mastery Learning System at Madrasah Aliyah Negeri 3 Jember - St. Mislikhah (Fenomena, 2017)
The implementation of mastery learning systems is a crucial approach in education; however, many schools still conduct remedial and enrichment programs inappropriately, such as only at the end of the semester. This study aims to describe the implementation of the mastery learning system to enhance student motivation at MAN 3 Jember, specifically focusing on remedial and enrichment programs, as well as supporting and inhibiting factors. A descriptive qualitative approach with purposive sampling was employed. Data were collected through non-participant observation, in-depth interviews, and documentation, then analyzed using the Miles and Huberman interactive model. The findings reveal that mastery learning is implemented through remedial programs for students failing to meet the minimum mastery criteria and enrichment programs for high-achieving students. Remedial programs effectively increased student motivation. The main inhibiting factors were limited time, energy, and student interest, while the supporting factor was student interest itself. It is recommended that teachers allocate specific time and employ more varied methods in implementing remedial and enrichment activities. Penerapan sistem pembelajaran tuntas menjadi pendekatan penting dalam dunia pendidikan, namun masih banyak sekolah melaksanakan program remedial dan pengayaan secara kurang tepat, seperti hanya dilakukan di akhir semester. Penelitian ini bertujuan mendeskripsikan implementasi sistem pembelajaran tuntas untuk meningkatkan motivasi belajar siswa di MAN 3 Jember, khususnya pelaksanaan remedial dan pengayaan serta faktor pendukung dan penghambatnya. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan teknik purposive sampling. Data dikumpulkan melalui observasi nonpartisipan, wawancara mendalam, dan studi dokumentasi, lalu dianalisis menggunakan model interaktif Miles dan Huberman. Hasil penelitian menunjukkan bahwa pelaksanaan pembelajaran tuntas dilakukan melalui program remedial bagi siswa yang belum mencapai standar ketuntasan belajar minimal (SKBM) dan program pengayaan bagi siswa yang cepat mencapai kompetensi. Program remedial terbukti mampu meningkatkan motivasi belajar siswa. Faktor penghambat utama adalah keterbatasan waktu, tenaga, dan minat siswa, sedangkan faktor pendukung adalah minat belajar siswa itu sendiri. Disarankan agar guru mengalokasikan waktu khusus dan menggunakan metode yang lebih variatif dalam pelaksanaan remedial dan pengayaan.